Development of an Adaptive Acquisition and Transmission System for Digital Processing of ECG Signals under Variable n-QAM Schemes - Cárdenas-Valdez, José Ricardo; Ramírez-Arzate, Fortunato; Corral-Domínguez, Ángel Humberto; Hurtado-Sánchez, Carlos; Calvillo-Téllez, Andrés; García-Guerrero, Enrique Efrén (Revista Mexicana de Ingenieria Biomedica, 2024)
In the post-pandemic era, it is critical to monitor and transmit biomedical signals, specifically ECG. This study aims to develop a platform that enables signal acquisition, adaptation, and transmission using different n-QAM modulation schemes. The system comprises an acquisition stage implemented in the 2.5 GHz band employing the Olimex module and electrodes equipped with an Ag/AgCl type sensor. To effectively manage appropriate bandwidths during implementation of the various n-QAM modulation schemes, an adaptive algorithm was developed and applied to the system. The power amplifier was operated in the linear region to enhance the crest factor and achieve an ACPR close to 30 dBc, demonstrating an appropriate demodulation of the electrocardiogram (ECG) signal, it is feasible to shift to modulation schemes above 64-QAM in order to detect high frequencies and perform a subsequent Fourier analysis. As a telemedicine proposal, the developed system offers flexibility in signal acquisition, data storage, and digitalization, in addition to a multivariable n-QAM scheme; the hardware implementation ensures n-QAM scheme compatibility. For the purpose of contributing to telemedicine via RF transmission, the system was executed on an AD9361 transceiver, which removes the requirement for a traditional signal vector generator and enables optimal control of the tones to be transmitted.